MEASURING DEVICES OF 3-MM WAVE-LENGTH RANGE - V. V. Murav’iov; S. A. Korenevsky; N. M. Naumovich (Приборы и методы измерений, 2015)
The problems of development as well as methods of construction of measuring devices of 3-mm wavelength range are examined, which allow to provide high degree of accuracy of frequency and power of an input signal measurement. The opportunity and expediency of using the frequency synthesizers, sub-harmonic mixers in heterodyne channel, and logarithmic amplifiers in modulation receiver are shown. The experimental parameters are shown as well as characteristics and parameters of major units of measuring device.